User-Generated Content, Online Trust, and Purchase Intention: An Empirical Study of Social Commerce Platforms - Van Dat, Nguyen; Hoang, Canh Chi; Khoa, Bui Thanh (Jurnal The Messenger, 2025)
Purpose: User-generated content (UGC) affected consumer trust and purchasing intention in social commerce platforms. It evaluated the growing influence of user-generated content on online consumer behavior and how online trust mediates the association between UGC and purchase intention. This study intended to understand how different types of UGC affect consumer trust and buy intentions, moving beyond previous studies' focus on individual UGC parts. Methods: A quantitative study design was utilized, employing Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were gathered via an online survey disseminated among persons in Vietnam who regularly engage with social commerce platforms. The questionnaire employed established multi-item scales derived from previous research to assess UGC, online trust, and buy intention. Findings: The findings demonstrated that user-generated content favorably impacted online trust, which subsequently enhanced purchase intention. UGC is essential for establishing trust and influencing purchasing decisions in social commerce. The model elucidated a significant variance in online trust and purchasing intention. Originality: This study shows how trust mediates the relationship between UGC and buy intention in social commerce, improving understanding of online consumer behavior. It stresses the importance of good UGC for consumer trust and purchase intention, giving valuable data for social commerce platforms and marketers. Future research may examine these findings in different cultures and examine other factors affecting consumer trust and purchase intention.